Effect of sodium-glucose transporter 2 inhibitors on sarcopenia in patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Zhang, Sha; Qi, Zhan; Wang, Yidong; Song, Danfei; Zhu, Deqiu (Frontiers in Endocrinology, 2023)
Objective: Sarcopenia has been recognized as the third category of disabling complications in patients with T2DM, in addition to micro- and macrovascular complications. Sodium-glucose co-transporter 2 (SGLT2) inhibitors have been shown to reduce body weight and enhance cardiovascular and renal outcomes. However, there is vigilance that SGLT2 inhibitors should be taken cautiously because they target skeletal muscle and may raise the risk of sarcopenia. Herein, we conducted a meta-analysis of randomized controlled trials to evaluate the effects of SGLT2 inhibitors on sarcopenia in patients with T2DM. Method: We searched PubMed, Embase, Medicine, Cochrane, and Web of Science databases to determine eligible studies. A random effects model was utilized irrespective of heterogeneity, and the I2 statistic was used to evaluate study heterogeneity. The differences in results were measured using the weighted average difference (WMD) of the continuous data, along with a 95% confidence interval (CI). Results: A total of 25 randomized controlled trials with 2,286 participants were included. SGLT2 inhibitors significantly reduced weight-related changes and fat-related changes, including body weight([WMD]= -2.74, [95% CI: -3.26 to -2.23], P<0.00001), body mass index([WMD] = -0.72, [95% CI: -0.95 to -0.49], P<0.00001), waist circumference([WMD] = -1.60, [95% CI: -2.99 to -0.22], P<0.0001), fat mass([WMD] = -1.49, [95% CI: -2.18 to -0.80, P<0.0001), percentage body fat([WMD] = -1.28, [95% CI: -1.83 to -0.74, P<0.00001), visceral fat area([WMD]=-19.51, [95% CI: -25.90 to -13.14], P<0.00001), visceral fat area ([WMD] = -19.11, [95% CI: -31.18 to -7.03], P=0.002), subcutaneous fat area ([WMD] = -19.11, [95% CI: -31.18 to -7.03], P<0.00001). In terms of muscle-related changes, lean mass([WMD] = -0.80, [95% CI: -1.43 to -0.16], P<0.0001), and skeletal muscle mass([WMD] = -0.38, [95% CI: -0.65 to -0.10], P=0.007), skeletal muscle index([WMD] = -0.12, [95% CI: -0.22 to -0.02], P=0.02) were also significantly reduced. Conclusions: SGLT2 inhibitors have beneficial effects on FM and BW weight loss in T2DM, such as BW, BMI, WC, FM, PBF, VFA, and SFA. However, the negative influence on muscle mass paralleled the reduction in FM and BW, and the consequent increased risk of sarcopenia warrants high attention, especially as patients are already predisposed to physical frailty.